The first mass drug administration campaign for schistosomiasis control in Lagos, Nigeria: lessons for future control programs - Olamiju, Francisca O.; Nebe, Obiageli; Mogaji, Hammed; Abdus-Salam, Ismail; Jenrola, Lanre; Marcus, Ayodele J.; Olamiju, Olatunwa J.; Isiyaku, Sunday; Amodu-Agbi, Perpetua; Nwoye, Ikenna; Achu, Ijeoma; Abah, Emmanuel (Frontiers in Tropical Diseases, 2023)
Background In this study we summarized the lessons learnt during the first effective mass drug administration (MDA) campaign in one of the most urbanized states in Nigeria. We particularly discuss the implementation approach including associated challenges and future prospects. Methods We implemented schistosomiasis MDA with praziquantel in seven endemic districts of the state, using a sub-district/ward-level implementation approach. Upon completion, we conducted desk reviews of field reports and a high-level stakeholder meeting among 95 key personnel involved in the MDA. We reviewed excerpts from the meetings to highlight the strengths, weaknesses, threats and opportunities (SWOT) of the sub-district/ward-level implementation approach. Quantitative data were summarized using basic descriptive statistics, while qualitative data were analyzed to identify emerging themes. Results About 1.45 million children between age 5 and 15 were targeted for treatment, and a geographic (100%) and therapeutic coverage of 85.5% was achieved. Therapeutic coverage was optimal (>75%), across all the implementation districts (Range:76.2- 95.3%). Ifako-Ijaiye had the highest therapeutic coverage (95.3%), while Oshodi-Isolo as the least (76.2%). Strategies supporting high coverage includes; (1) adequate delineation of hard-to reach areas and allocation of commensurate resources, (2) improved consultation and microplanning among programmers, (3) addressing traffic congestion on transportation routes, (4) strengthened engagements and collaborations with community gatekeepers, (5) optimizing cash flow to mitigate financial risk, (6) capacity building of field stakeholders and, (7) regular advocacy and sensitization among stakeholders. Conclusion This study provides possible directions for implementation of schistosomiasis control by programs and agencies at sub-district/ward-level in a cosmopolitan and urbanized state, like that of Lagos, Nigeria.